A tenascin-C mimetic peptide amphiphile nanofiber gel promotes neurite outgrowth and cell migration of neurosphere-derived cells. (June 2016) - Berns, Eric J.; Álvarez, Zaida; Goldberger, Joshua E.; Boekhoven, Job; Kessler, John A.; Kuhn, H. Georg; Stupp, Samuel I.
Graphical abstract: Abstract: Biomimetic materials that display natural bioactive signals derived from extracellular matrix molecules like laminin and fibronectin hold promise for promoting regeneration of the nervous system. In this work, we investigated a biomimetic peptide amphiphile (PA) presenting a peptide derived from the extracellular glycoprotein tenascin-C, known to promote neurite outgrowth through interaction with β1 integrin. The tenascin-C mimetic PA (TN-C PA) was found to self-assemble into supramolecular nanofibers and was incorporated through co-assembly into PA gels formed by highly aligned nanofibers. TN-C PA content in these gels increased the length and number of neurites produced from neurons differentiated from encapsulated P19 cells. Furthermore, gels containing TN-C PA were found to increase migration of cells out of neurospheres cultured on gel coatings. These bioactive gels could serve as artificial matrix therapies in regions of neuronal loss to guide neural stem cells and promote through biochemical cues neurite extension after differentiation. One example of an important target would be their use as biomaterial therapies in spinal cord injury. Statement of Significance: Tenascin-C is an important extracellular matrix molecule in the nervous system and has been shown to play a role in regenerating the spinal cord after injury and guiding neural progenitor cells during brain development, however, minimal research has been reported exploring the use of biomimetic biomaterials of tenascin-C. In this work, we describe a selfassembling biomaterial system in which peptide amphiphiles present a peptide derived from tenascin-C that promotes neurite outgrowth. Encapsulation of neurons in hydrogels of aligned nanofibers formed by tenascin-C-mimetic peptide amphiphiles resulted in enhanced neurite outgrowth. Additionally, these peptide amphiphiles promoted migration of neural progenitor cells cultured on nanofiber coatings. Tenascin-C biomimetic biomaterials such as the one described here have significant potential in neuroregenerative medicine.